PENGARUH PENAMBAHAN ALTERNATE NOSTRIL BREATHING PADA SENAM AEROBIC LOW IMPACT TERHADAP PENDERITA HIPERTENSI LANSIA - Asyhara Neaela Arifin; Reda Okta Yana; Ummy Aisyah Nurhayati (Jurusan Fisioterapi Poltekkes Kemenkes Surakarta, 2024)
Background: The elderly are an age group that is vulnerable to disease. They will experience physiological disorders that affect the blood vessels which will then resultin hypertension. To lower blood pressure, there are many exercises to do, one of whichis the alternate nostril breathing technique and low-impact aerobic exercise. Objective: The study aims to determine the effect of adding alternatenostril breathing to low-impact aerobic exercise on the elderly with hypertension. Method:The research used a quasi-experimental with a two-group pretest andposttest design, the sampling technique used was purposive sampling, the sample was30 people with an exercise program 3 times a week for 3 weeks. Group I was given the low impact aerobic exercise and Group II was given the addition of alternatenostril breathing to low-impact aerobic exercise. The measuring instrument in the research was a sphygmomanometer. Result: The hypothesis I test (p < 0.05) showed that there was an effect of low-impact aerobic exercise on elderly with hypertension, hypothesis II test (p < 0.05) showed that there was an effect of the addition of alternate nostril breathing to low-impact aerobic exercise on elderly with hypertension. Conclusion: There is an effect of adding alternate nostril breathing to low-impact aerobic exercise on elderly with hypertension.